Investigating lactoferrin and somatic cell count dynamics in early postpartum Shami and Baladi goats - Ali, Montaser Elsayed; Abdelrahman, Mohamed; Zakaria, Asem Mohammed; Farag, Belal Farrag; Mohamed, Ragab Hassan; Fayed, Hayat; El-Hamid, Ibrahim Samir Abd; Ali, Fatma; Gheetas, Rabee M.; Nour, Safaa Y.; Alsyaad, Khalid M.; Gao, Min (Frontiers in Veterinary Science, 2025)
Earlier studies found that milk lactoferrin (LF) concentration was significantly associated with somatic cell count (SCC) dynamics and lactation stage was related to milk production and mammary gland health, which helps determine the physiopathological conditions and goats’ postpartum activity. The presented study aimed to design an integrated monitoring system among LF and SCC dynamics and hematological indices over the postpartum timeline in Baladi and Shami goats. After collecting the data, the Shami and Baladi groups were compared using independent t-tests, and Pearson’s correlation analysis was performed between variables. This study reported that Shami and Baladi goats’ LF concentrations and SCC had fallen incrementally from day 1 to 35 days postpartum (DPP), and both LF and SCC showed (p < 0.05) correlation in early DPP. However, Baladi goats were significantly higher (p < 0.01) in milk yield, fat percentage, and protein at 15 DPP than Shami goats. Also,no significant differences (p > 0.05) were found in salts, solids, not fat, and total solids between the two groups at 35 DPP. However, total protein, albumin, and globulin-related parameters were significantly higher (p < 0.01) at 15 DPP in Baladi compared to Shami goats. The Baladi goats were significantly higher for energy-related parameters and total protein and globulin-related parameters at 35 DPP. As expected, some correlation (p < 0.05) between LF and SCC was also seen during early DPP. Furthermore, Shami goats lymphocytes (LYM) × 103/μL, granulocytes (GRA), hemoglobin (HGB), and mean corpuscular hemoglobin concentration (MCHC) were significantly higher (p < 0.05) at 15 DPP. Also, at 35 DPP, white blood cells (WBC), lymphocytes (LYM), and monocytes (MONO) were lower in the Shami goats. In conclusion, this study provides essential physiological benchmarks for tracking goat lactation recovery by showing distinctive patterns of lactoferrin and somatic cell count dynamics and hematological adaptation during the postpartum period.